2019
DOI: 10.3390/ijerph16112050
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Smoking Cessation Care into a Medically Supervised Injecting Facility Using an Organizational Change Intervention: A Qualitative Study of Staff and Client Views

Abstract: Background: Clients accessing supervised injecting facilities (SIFs) smoke at high rates. An SIF piloted an organizational change intervention to integrate smoking cessation care as routine treatment. This study aims to explore staff acceptability, perceived facilitators, and perceived barriers to implementing six core components of an organizational change intervention to integrate smoking cessation care in an SIF. Staff and client views on the acceptability, facilitators, and barriers to the provision of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This same patterning of results has also been more broadly reported (Baca & Yahne, 2009; Friend & Pagano, 2005; McKelvey et al, 2017; Piper, Kenford, Fiore, & Baker, 2012), and suggests that smoking cessation and even reductions in tobacco use may be associated with enhanced drug treatment outcomes. This is an important finding since integration of smoking cessation care in drug treatment settings is low (Skelton et al, 2019), and patients’ and treatment providers’ concerns about sobriety may still serve as substantial barriers to smoking cessation efforts during addiction treatment (Fine, Bearnot, Rigotti, & Baggett, 2019; González-Roz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This same patterning of results has also been more broadly reported (Baca & Yahne, 2009; Friend & Pagano, 2005; McKelvey et al, 2017; Piper, Kenford, Fiore, & Baker, 2012), and suggests that smoking cessation and even reductions in tobacco use may be associated with enhanced drug treatment outcomes. This is an important finding since integration of smoking cessation care in drug treatment settings is low (Skelton et al, 2019), and patients’ and treatment providers’ concerns about sobriety may still serve as substantial barriers to smoking cessation efforts during addiction treatment (Fine, Bearnot, Rigotti, & Baggett, 2019; González-Roz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A single‐site, pre‐ to post‐intervention, mixed‐methods study showed that staff‐reported smoking cessation practices significantly increased for the provision of verbal advice (30–82%), offer of free or subsidized nicotine replacement therapy (30–91%), referral to a general practitioner (19–64%) and follow‐up to check on quit smoking progress (18.5–64%). More than 85% of staff agreed that it was acceptable to address smoking as part of usual care and 95% of people in treatment agreed that it was acceptable to be asked by staff about their tobacco smoking . However, no randomized controlled trials have been conducted of the effectiveness of the approach at improving cessation rates among smokers in AOD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It includes changing health information technology, integrating documentation into existing workflows, engaging clinical support staff, or increasing training to build staff capacity (Flocke et al, 2020). Health systems change innovations for tobacco treatment have been implemented and examined in hospitals (Trapskin et al, 2022), outpatient clinics (Baker et al, 2021; Flocke et al, 2020; Jansen et al, 2014; Thomas et al, 2017), oncology clinics (Gali et al, 2020), behavioral health sites (Bloom et al, 2018; Himelhoch et al, 2014), supervised injecting facilities (Skelton et al, 2019), integrated health systems (Jansen et al, 2014; Whittet et al, 2019), and dental clinics (Thomas et al, 2017; Whittet et al, 2019). Although health systems change innovations for tobacco treatment have been implemented across a range of settings, most studies examining such innovations are limited to one setting (Baker et al, 2021; Bloom et al, 2018; Flocke et al, 2020; Gali et al, 2020; Himelhoch et al, 2014; Skelton et al, 2019; Thomas et al, 2017; Trapskin et al, 2022).…”
mentioning
confidence: 99%
“…Health systems change innovations for tobacco treatment have been implemented and examined in hospitals (Trapskin et al, 2022), outpatient clinics (Baker et al, 2021; Flocke et al, 2020; Jansen et al, 2014; Thomas et al, 2017), oncology clinics (Gali et al, 2020), behavioral health sites (Bloom et al, 2018; Himelhoch et al, 2014), supervised injecting facilities (Skelton et al, 2019), integrated health systems (Jansen et al, 2014; Whittet et al, 2019), and dental clinics (Thomas et al, 2017; Whittet et al, 2019). Although health systems change innovations for tobacco treatment have been implemented across a range of settings, most studies examining such innovations are limited to one setting (Baker et al, 2021; Bloom et al, 2018; Flocke et al, 2020; Gali et al, 2020; Himelhoch et al, 2014; Skelton et al, 2019; Thomas et al, 2017; Trapskin et al, 2022). Furthermore, no study has examined TTS implementation as a specific component of health systems change nor applied a theoretical perspective to comprehensively examine factors that may influence sustainability of TTSs.…”
mentioning
confidence: 99%